How Functional Reviews in the Health Sector Exacerbated Occupational Stress and Burnout Among Clinical Officers at Public Hospitals in Malawi - Paliani Chinguwo (Clinical Sociology Review)
In Malawi, there is a cadre of mid-level health professionals called clinical officers. In the wake of an acute shortage of medical doctors, clinical officers perform tasks conventionally designated for medical doctors. This paper seeks to explain how the implementation of some functional reviews in the health sector, exacerbated occupational stress (OS) and burnout among clinical officers at public hospitals in Malawi. The study adopted a qualitative research design with a case study as a research strategy. The study was conducted at four district hospitals and one central hospital, all of which are state-owned in Malawi. The paper argues that the implementation of some functional reviews, is a psychosocial hazard among clinical officers at public hospitals. The paper demonstrates that the implementation of some functional reviews, has aggravated occupational stress and burnout among clinical officers at public hospitals. The paper concludes that the implementation of some functional reviews, has perpetuated interprofessional conflicts between clinical officers and medical doctors; forms of occupational violence by doctors against clinical officers; loss of power and an identity crisis among clinical officers. The paper, therefore, argues that interprofessional conflicts, occupational violence, loss of power and identity crisis were ultimately drivers of occupational stress and burnout among clinical officers. Finally, the paper recommends that a psychosocial risk assessment, should be conducted to avoid or minimise the risks of occupational stress and burnout among clinical officers that are posed by the implementation of functional reviews in the health sector.